Вакуумная перегонка как основной метод регенерации гидравлических масел - Григоров, Андрей Борисович (НТУ "ХПИ", 2012)
In article the review on domestic and foreign methods of regeneration of the fulfilled hydraulic oils is resulted. Advantages of application of vacuum distillation are described by the example of regeneration of oils of marks «TOC Hydraulic HLP 46» and «ROWE HLP 46», the fulfilled 500 hours per hydraulic systems automatic lines.
Keywords: смазочные материалы; отработанные масла; регенерация масел; гидравлические масла; блок вакуумной перегонки; вакуумная колонна; роторно-пленочный аппарат